2017
DOI: 10.1007/s11150-017-9385-x
|View full text |Cite
|
Sign up to set email alerts
|

Single-mother families and the gender gap in children’s time investment and non-cognitive skills

Abstract: This paper analyzes the role of family structure in the gender gap in children's time investment in studying and non-cognitive skills. We focus on Italy, a country that, similar to many other OECD countries, is experiencing both an increasing number of single-parent families (most of which are headed by mothers) and an increasing gender gap in children's cognitive and non-cognitive outcomes. By using a difference-indifferences specification comparing children's outcomes in singleversus two-parent families for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 44 publications
(51 reference statements)
2
27
0
1
Order By: Relevance
“…16 e.g. Mencarini et al (2019). 17 Adams-Prassl et al (2020) find evidence of this for the U.S., U.K., and Germany.…”
Section: Specificationmentioning
confidence: 98%
See 1 more Smart Citation
“…16 e.g. Mencarini et al (2019). 17 Adams-Prassl et al (2020) find evidence of this for the U.S., U.K., and Germany.…”
Section: Specificationmentioning
confidence: 98%
“…E.g.,Porterfield and Winkler (2007),Guryan et al (2008),Wight et al (2009), andDotti et al (2016).4 See references in previous footnote as well asRamey and Ramey (2010),Heckman and Mosso (2014), andMencarini et al (2019).Covid-19 shocks to education supply: how 200,000 U. S. households dealt with the sudden. .…”
mentioning
confidence: 99%
“…This is particularly worrying as this four-month reduced activity period adds straight to the usual three-month inactivity period of Italian school during summertime. In addition, the effect is likely to be heterogeneous not only by family socio-economic status and level of education (Mancini et al, 2017;Mencarini et al, 2019), but also by age of the children. In fact, while about 95% of children attending secondary school had access to distance education classes and material, for primary school the school ability to provide distance education was much more limited and quite heterogeneous.…”
Section: Children Emotional and Educational Wellbeingmentioning
confidence: 99%
“…Studies with US data found that female teenagers are more active in domestic chores, reading and doing homework, while male teenagers are more involved in screen-based activities (Wight et al, 2009). Research using Italian data found that girls spend less time than boys on active leisure and sports, and more time on domestic chores, with gender differences increasing remarkably from childhood to youth (Dotti-Sani, 2018;Mencarini et al, 2019). In a study with Canadian data, boys and girls were also found to have gendered leisure patterns (Hilbrecht et al, 2008).…”
Section: Introductionmentioning
confidence: 96%